Pendidikan awam untuk pemuliharaan warisan: kajian kes Langkawi Geopark - Norzaini Azman,; Ibrahim Komoo,; Sharina Abdul Halim,; Ruslin Amir, (Universiti Kebangsaan Malaysia, 2010)
This article discusses the research findings on public education for heritage conservation. The research aims to determine the level of awareness and understanding on geopark and heritage conservation from the perspectives of the various stakeholders. The data gathered from the study serves as important baseline information in preparing tools and mechanism for public education as well as educational tools and programmes to promote understanding and awareness among the various stakeholders of geopark. This research also seeks to summarise various approaches to non-formal education and awareness programmes from local community. The sample comprises various stakeholders, namely the local authorities, hoteliers and resort managers, tourist operators and tourists, local community, students and teachers. The findings of the study indicate relatively low levels of awareness and understanding among the stakeholders mainly regarding the geopark concept, heritage conservation and role of Langkawi geopark in the local community socioeconomic development activities. Thus, effective and innovative development tools and public educational mechanisms are crucial to address the findings of this study. The development of tools and mechanisms for public education must give emphasis to: 1) level of understanding of the targeted group in developing content; 2) inculcation of shared values particularly those that bring benefits to regional sustainable development and community livelihood; 3) conservation of geological, biological and cultural heritage should initially be separately taught, but eventually, these components must be taught in an integrated manner; 4) introduction of tourism-based products related to geopark; and 5) education on geopark in schools should be systematically planned and implemented. Suffice to say that the development of the approaches and strategies for effective public education must give priority to the needs, interest and abilities of the target groups i.e. the stakeholders for optimal effectiveness of public education programmes.